AN ANALYTICAL STUDY ON THE AWARENESS OF SCHEDULED TRIBE (ST) WOMEN REGARDING THE PESA ACT AND THEIR CONTRIBUTION TO THE BENEFITS RECEIVED - SPECIAL REFERENCE TO GADCHIROLI DISTRICT - Khandekar, Pankaj; Vasnik, Kishore B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study will investigate the awareness level of Scheduled Caste (ST) women in Gadchiroli district regarding the provisions of Panchayat (Expansion of Scheduled Areas) (PESA) Act, 1996 and their role in availing the benefits provided under the Act. The researchers rely on a combination of surveys, interviews and targeted group discussions to assess their knowledge base, participation in local governance and challenges in accessing PESA benefits. Conclusions It has been seen that while some Scheduled Tribe women are actively participating in village council meetings and decision making processes, a significant gap in knowledge remains due to socio-cultural barriers, limited education and incomplete inclusion efforts. The study highlights the need for targeted awareness programs, increased representation of women in administration and policy interventions to enable women belonging to Scheduled Tribes to effectively utilize PESA funds. Strengthening their role in self-governance will go a long way in improving social and economic development of tribal communities.